2019
DOI: 10.1002/oby.22472
|View full text |Cite
|
Sign up to set email alerts
|

Are Liquid Sugars Different from Solid Sugar in Their Ability to Cause Metabolic Syndrome?

Abstract: Objective: Intake of sugary drinks, especially soft drinks, carries increased risk for obesity and diabetes. This article reviews whether sugary drinks carry different risks for metabolic syndrome compared with foods that contain natural or added sugars. Methods: A narrative review was performed to evaluate differences between liquid and solid sugars in their ability to induce metabolic syndrome and to discuss potential mechanisms to account for the differences. Results: Epidemiological studies support liquid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 97 publications
2
46
0
2
Order By: Relevance
“…Recently, a clinical study placed subjects on a high-sugar, high-fat diet with a more healthy diet, and found that at 4 days an impairment in short term memory and hippocampal function could be shown in the high sugar, high-fat diet group (Attuquayefio et al, 2017 ). The observation that total and liquid sugars are more likely associated with cognitive dysfunction is consistent with studies showing that liquid sugars cause more significant ATP depletion and metabolic effects, while the negative studies with natural fruits are also consistent given the presence of antioxidants and flavonols in fruits that are known to counter fructose effects (Sundborn et al, 2019 ).…”
Section: Fructose Metabolism and Alzheimer’s Diseasesupporting
confidence: 78%
See 1 more Smart Citation
“…Recently, a clinical study placed subjects on a high-sugar, high-fat diet with a more healthy diet, and found that at 4 days an impairment in short term memory and hippocampal function could be shown in the high sugar, high-fat diet group (Attuquayefio et al, 2017 ). The observation that total and liquid sugars are more likely associated with cognitive dysfunction is consistent with studies showing that liquid sugars cause more significant ATP depletion and metabolic effects, while the negative studies with natural fruits are also consistent given the presence of antioxidants and flavonols in fruits that are known to counter fructose effects (Sundborn et al, 2019 ).…”
Section: Fructose Metabolism and Alzheimer’s Diseasesupporting
confidence: 78%
“…However, the remarkable increase in sugar and HFCS intake has led to excessive and chronic activation of this pathway, resulting in increased risk for metabolic syndrome, obesity, and diabetes ( Figure 2 ; Johnson et al, 2013 ). The risk is particularly high with liquid sugars, such as soft drinks, as the high fructose content coupled with rapid intake leads to high concentrations in the liver that can lead to more profound intracellular energy depletion (Sundborn et al, 2019 ). While dietary fructose is a major source of fructose, endogenous production of fructose may also drive the metabolic syndrome, such as in response to high glycemic carbohydrates and high salt diets (Lanaspa et al, 2013 , 2018 ).…”
Section: Recent Insights In Fructose Metabolismmentioning
confidence: 99%
“…Sugars in juice are absorbed more quickly than those in fruit and vegetables, which are absorbed more slowly due in part to their fiber content [95,96]. The rapid absorption of liquid fructose (from juice) compared to solid forms is more likely to result in higher concentrations of fructose in the liver and increase the rate of hepatic extraction of fructose, de novo lipogenesis, and production of lipids [97,98]. A recent study in the REGARDS cohort found that fruit juice intake was associated with a higher risk of all-cause mortality [62].…”
Section: Alternative Beveragesmentioning
confidence: 99%
“…Mice were fasted for 5 hours prior to intraperitoneal injection with insulin Humulin R (Eli Lilly, IN, USA) at 0.7 IU/kg body weight or 0.5 IU/kg body weight for males and females, respectively. Blood glucose levels were taken from tail vein using a Freestyle Lite glucometer (Abbott, IL, USA) at 0, 15,30,45,60,90 and 120 minutes post-injection.…”
Section: Nash Cohort Diets and Micementioning
confidence: 99%